2008
DOI: 10.1515/bc.2008.103
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity after allogeneic hematopoietic stem cell transplantation

Abstract: The postulated almost unlimited potential of transplanted hematopoietic stem cells (HSCs) to transdifferentiate into cell types that do not belong to the hematopoietic system denotes a complete paradigm shift of the hierarchical hemopoietic tree. In several studies during the last few years, donor cells have been identified in almost all recipient tissues after allogeneic HSC transplantation (HSCT), supporting the theory that any failing organ could be accessible to regenerative cell therapy. However, the puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 91 publications
0
7
0
1
Order By: Relevance
“…1 In 1965, Medawar 2 hypothesized that longterm acceptance of solid organ transplants may be the result of replacement of their vascular endothelial cells by recipient-type cells leading to an endothelial cell chimerism. In particular, bone marrow-derived endothelial progenitor cells may replace damaged graft endothelium after rejection episodes.…”
Section: Introductionmentioning
confidence: 99%
“…1 In 1965, Medawar 2 hypothesized that longterm acceptance of solid organ transplants may be the result of replacement of their vascular endothelial cells by recipient-type cells leading to an endothelial cell chimerism. In particular, bone marrow-derived endothelial progenitor cells may replace damaged graft endothelium after rejection episodes.…”
Section: Introductionmentioning
confidence: 99%
“…In skin, studies have shown that BM provides fibroblast-like cells in the dermis (of hematopoietic and mesenchymal lineages) and that the number of these cells increases after skin wounding (3,4). BM can also generate epithelial cells, i.e., keratinocytes, in the epithelia, although the precise derivations and mechanisms to raise BM-derived keratinocytes are not fully known (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Human/mouse studies involving transplantation of sex-mismatched or genetically tagged BM cells have shown that keratin-positive bone marrow-derived cells can be found in skin epidermis, hair follicles, and sebaceous glands (6,8,9,11,12,14,16), sites that harbor skin stem cell niches (17).…”
mentioning
confidence: 99%
“…4 In healthy animals tissue injury induces cytokine expression to stimulate bone marrow-derived stem cells to emerge in the blood, migrate into injured tissues, and participate in tissue regeneration. [28][29][30][31] As autoimmune disease causes inflammation-mediated tissue injury, we hypothesized that elevated levels of MMc found in patients could be secondary to non-specific signals of inflammation or tissue injury, and thus a result, rather than a cause of chronic inflammation. We found in two distinct models of renal injury that maternal cells are not increased (either by expansion or recruitment) in response to tissue injury, inflammation, regeneration or fibrosis.…”
Section: Discussionmentioning
confidence: 99%